Current Proceedings of Childhood Stroke - Hueng-Chuen Fan; Chih-Fen Hu; Chun-Jung Juan; Shyi-Jou Chen (Stroke Research and Treatment)
Stroke is a sudden onset neurological deficit due to a cerebrovascular event. In children, the recognition of stroke is often delayed due to the low incidence of stroke and the lack of specific assessment measures to this entity. The causes of pediatric stroke are significantly different from that of adult stroke. The lack of safety and efficiency data in the treatment is the challenge while facing children with stroke. Nearly half of survivors of pediatric stroke may have neurologic deficits affecting functional status and quality of life. They may cause a substantial burden on health care resources. Hence, an accurate history, including onset and duration of symptoms, risk factors, and a complete investigation, including hematologic, neuroimaging, and metabolic studies is the key to make a corrective diagnosis. A prompt and optimal treatment without delay may minimize the damage to the brain.